2015
DOI: 10.1002/andp.201500132
|View full text |Cite
|
Sign up to set email alerts
|

Localized EM and photonic jets from non‐spherical and non‐symmetrical dielectric mesoscale objects: Brief review

Abstract: The interest to mesoscale dielectric objects, whose effective dimensions are comparable with the incident radiation wavelength, is caused by their unique ability to modify the spatial structure of the incident wave in the specific manner and to produce a highly localized intensive optical flux ("photonic jet") with the subwavelength spatial resolution. In the current paper we brief review the modern state-ofthe-art of main principles of the photonic jet formation by non-spherical and non-symmetrical dielectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 32 publications
1
59
0
2
Order By: Relevance
“…In this context photonic nanojet was first introduced by Zhigang Chen et al in 2004 [1]. Due to its immense importance in various optical applications, lots of research outcomes and reviews are frequently reported [2,3,4]. These articles are mainly focused on photonic nanojet which is nothing but the enhancement of Mie scattering to form a highly intense, low diverge and weak sub diffract waist light beam generated from a microstructure.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this context photonic nanojet was first introduced by Zhigang Chen et al in 2004 [1]. Due to its immense importance in various optical applications, lots of research outcomes and reviews are frequently reported [2,3,4]. These articles are mainly focused on photonic nanojet which is nothing but the enhancement of Mie scattering to form a highly intense, low diverge and weak sub diffract waist light beam generated from a microstructure.…”
Section: Introductionmentioning
confidence: 98%
“…However the maximum dimension of this type of microstructures can be ten times that of the incident wave length. Currently various microstructures such as sphere [5], cylinder [6], ellipsoid [7,8], axicon [4,9], cuboids [10], microdisk [11] and there modified structures such as sections [12] , layer (graded [13], liquid immerged [14,15], metal coated [16]) or their chain [17] are also able to generate photonic nanojet. Out of these, sphere shaped micro structure has the ability to generate high intense nanojet however axicon shaped micro structure gives the highest propagation length in free space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the photonic nanojet shaping by a simple and cheap way is an interesting research topic for the far-field projection system. The non-spherical micromedia of various spatial shapes, such as microellipses, microcones, micropyramids and microcuboids, have been intensely studied in recent years [21][22][23][24][25][26][27][28][29][30][31][32]. Such non-spherical micro-media are very attractive because they have unique ability to modify the spatial distribution of the lightwave in specific formations.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Recently, the study of terajets-the generation of photonic jets [20][21][22] in the THz frequency band-has attracted considerable research interest because of its capability of obtaining a subwavelength hotspot with mesoscale dielectric particles. 23,24 The initial studies on terajet generation were based on spheroids and the well-known Mie scattering theory. 20,25,26 Later, researchers found out-both theoretically and experimentally-that cuboids can generate terajets 27 with some advantages over spheroid-generated terajets from the point of view of the imaging application, such as more symmetric hotspots.…”
Section: Introductionmentioning
confidence: 99%